2023
DOI: 10.3389/fimmu.2023.1309015
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes as a potential therapeutic approach in osteoimmunology

Ivan V. Zhivodernikov,
Yuliya V. Markina,
Tatiana V. Kirichenko
et al.

Abstract: Exosomes are natural extracellular vesicles that play a key role in inter- and intracellular communication. Currently they are considered as a promising therapeutic strategy for the treatment of various diseases. In osteoimmunology, exosomes can serve as biomarkers of bone homeostasis disorders and, at the same time, promising therapeutic agents with high stability in the biological environment, low immunogenicity and good bioavailability. In this review, we attempted to examine exosomes as natural mediators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…In summary, immune cells serve as a link between gut microbiota and bone metabolism, modulating bone formation or resorption through the regulation of T or B cell functions. With the gradual emergence of the concept of osteoimmunology in recent years, gut microbiota serve as a vital link in exploring the connection between bone and the immune system, offering additional targets for the treatment of bone metabolism disorders ( Sharma et al., 2023 ; Zhivodernikov et al., 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…In summary, immune cells serve as a link between gut microbiota and bone metabolism, modulating bone formation or resorption through the regulation of T or B cell functions. With the gradual emergence of the concept of osteoimmunology in recent years, gut microbiota serve as a vital link in exploring the connection between bone and the immune system, offering additional targets for the treatment of bone metabolism disorders ( Sharma et al., 2023 ; Zhivodernikov et al., 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on differences in EV generation, size, or function, they can be categorized into different subgroups such as exosomes, microvesicles, and apoptotic bodies. Exosomes are small, particle-like vesicles with a diameter of 30–150 nm formed by budding inward [ 3 ]. Previous research has unequivocally demonstrated the efficacy of exosomes in facilitating the process of bone repair.Exosomes derived from sources such as dexamethasone, osteogenic induction conditioned medium [ 4 ], and Curcumin-preconditioned Mesenchymal Stem Cells (MSCs) exhibit a remarkable capacity to stimulate osteogenesis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%